The Vaginal Colonization of Group B Streptococcus in Females in the Third Trimester of Their Pregnancy - Halil Ozerol, Ibrahim; Baysal, Bulent; Sengil, A.Zeki (Annals of Medical Research, 2021)
None
Keywords: s/b : Group B streptococcus, Streptococcus agalactiae, newborn disease, vaginal colonization.